Telaah Ayat Tentang Iddah dengan Pendekatan Interpretasi Kontekstual Abdullah Saeed dalam Perspektif Maqashid Syari‘ah - Firmansyah, Heri; Hizbullah, Muhammad; Haidir, Haidir (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Abdullah Saeed offers a method for understanding Quranic verses. He encourages readers and interpreters of the Quran not to passively accept the text but actively participate in giving meaning to the text. This article aims to examine the verses on iddah (waiting period after the death of a husband) using Abdullah Saeed's conceptual interpretation approach. Two specific verses are the focus of this study. The findings of this examination are then analyzed within the perspective of Maqashid Syariah, particularly in terms of the preservation of religion and lineage, known as maqashid ad-dharuriyah or maslahah ad-dharuriyyah. The study concludes that the iddah period for women whose husbands have passed away, which is traditionally four months and ten days, should be adjusted to the present conditions, considering the significant number of women who work outside their homes. The iddah period is understood to prohibit remarriage for women but allows them to leave the house and adorn themselves according to the atmosphere and needs of the workplace. The study findings on the iddah period for wives whose husbands have passed away, based on the analysis of the two examined verses, are found to align with the spirit of Maqashid Syariah, which focuses on the welfare of the wife.